PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PONOROGO CERDAS (STUDI PADA MUSTAHIQ BAZNAS PONOROGO) - Ayu Putri, Arina; Muttaqin, Aminullah Achmad (Islamic Economics and finance in Focus, 2022)
Zakat funds have a function to distribute their funds to community groups who are unable or mustahik in community empowerment or only consumptive funds are given for direct consumption. Zakat funds can also be channeled for education costs in the form of scholarships for poor people. This research was conducted in the district with the aim of researching community empowerment through the Education scholarship program at Baznas Ponorogo Regency. In this study using a qualitative approach. This research is an activity that must carry out a survey in the field to identify information and conditions that are carried out there. For this reason, the right approach is qualitative because it can reveal various information with careful and meaningful description-analysis, providing complex details about phenomena that are difficult to express. The result of this research is the Smart Ponorogo Program launched by BAZNAS Ponorogo in order to improve community empowerment so that the quality of life of the community becomes better and runs effectively, this information is supported by several informants. Behind this success, there are obstacles that are still a lot of lack of public understanding of zakat in BAZNAS, and the lack of public knowledge about the management of zakat funds at BAZNAS. There are also factors that support this program to run smoothly because of the collaboration between parents and schools as well as the cooperation of scholarship recipients